Model totem pole made by Ralph Bennett, ca. 1980 (1980)
Ralph Alfred Bennett, Goo la'Slacoon (b. 1949) is a local carver and his name translated means "Abalone Fingers." He is a fifth generation woodcarver from the Haida tribe in British Columbia. The eagle, bear, and beaver featured in this model totem pole are representative of Bennett's Haida heritage. 1 Pole, Totem; Materials: cedar --shell; Dimensions: 24.25 in.H x 7.5 in.W x 5.25 in.D